STORYTELLING IN TEACHING LITERACY: BENEFITS AND CHALLENGES - Intan Satriani (University of Kuningan, 2019)
Literacy has become a crucial position in education, especially in Indonesia. It is used as one of ways to develop education through developing the culture of reading, writing, and counting. The study aims to find out benefits and challenges of implementing storytelling in teaching literacy. The study employed a qualitative descriptive research design. The data were obtained from students’ interview and observation. The findings found some benefits in implementing teaching program which include using two languages as the medium of interaction, providing suitable learning materials and various media, using of dramatization to show a character’s expression, asking moral value of the story as an evaluation instrument, developing students’ literacy ability, arousing students’ imagination, enriching students’ vocabulary, and developing students’ reading awareness and interest. Meanwhile, some challenges found in implementing teaching program are students’ proficiency and length of texts. Based on those findings, it is suggested to provide more times to truly explore students’ literacy ability and their preference in story.